(untitled) (Revista Inclusiones, 2019)
The purpose of this research is to examine stakeholders on school principals’ readiness for the role of technology in school management and development. In this study, the case study method was used within the merits of the qualitative research approach.The data was collected by interview technique and document analysis (research diary). The results of the research indicate that there are effect on the reflection of socio-economic, cultural and technological changes in the society to school management, school manager has a great role to the technology use and compliance and teachers are facilitators to diffuse technology for the school management and development.